Clinical trials for Chagas disease: etiological and pathophysiological treatment - Gonzaga, Beatriz Matheus de Souza; Ferreira, Roberto Rodrigues; Coelho, Laura Lacerda; Carvalho, Anna Cristina C.; Garzoni, Luciana Ribeiro; Araujo-Jorge, Tania C. (Frontiers in Microbiology, 2023)
Chagas disease (CD) is caused by the flagellate protozoan Trypanosoma cruzi. It is endemic in Latin America. Nowadays around 6 million people are affected worldwide, and 75 million are still at risk. CD has two evolutive phases, acute and chronic. The acute phase is mostly asymptomatic, or presenting unspecific symptoms which makes it hard to diagnose. At the chronic phase, patients can stay in the indeterminate form or develop cardiac and/or digestive manifestations. The two trypanocide drugs available for the treatment of CD are benznidazole (BZ) and nifurtimox (NFX), introduced in the clinic more than five decades ago. WHO recommends treatment for patients at the acute phase, at risk of congenital infection, for immunosuppressed patients and children with chronic infection. A high cure rate is seen at the CD acute phase but better treatment schemes still need to be investigated for the chronic phase. There are some limitations within the use of the trypanocide drugs, with side effects occurring in about 40% of the patients, that can lead patients to interrupt treatment. In addition, patients with advanced heart problems should not be treated with BZ. This is a neglected disease, discovered 114 years ago that still has no drug effective for their chronic phase. Multiple social economic and cultural barriers influence CD research. The high cost of the development of new drugs, in addition to the low economical return, results in the lack of investment. More economic support is required from governments and pharmaceutical companies on the development of more research for CD treatment. Two approaches stand out: repositioning and combination of drugs, witch drastically decrease the cost of this process, when compared to the development of a new drug. Here we discuss the progress of the clinical trials for the etiological and pathophysiological treatment for CD. In summary, more studies are needed to propose a new drug for CD. Therefore, BZ is still the best option for CD. The trials in course should clarify more about new treatment regimens, but it is already possible to indicate that dosage and time of treatment need to be adjusted.